CONTENT AND ESSENCE OF CHILDREN'S EDUCATION IN PRE-SCHOOL EDUCATIONAL INSTITUTIONS (Ta'limning zamonaviy transformatsiyasi, 2024)
In this article, children in preschool educational institutions by teaching them the secrets of music in education awakening, spiritual maturity, physical training, enjoyment training has been reflected.